PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA PT TASINDO TOTAL INPRODUCTS DI KOTA BATAM - Herlini, Herlini; Purba, Tiurniari (SCIENTIA JOURNAL, 2021)
Advances in technology and science today, resulted in world economic activity growing rapidly. The existence of free trade provides the possibility of competition between companies. The purpose of this study was to determine the effect of promotion and service quality on purchasing decisions. The method used is descriptive statistical analysis with SPSS version 26. The results of the t test (partial) that the promotion has a positive and significant effect on purchasing decisions with t count > t table with a significance value < 0.05, namely 2.002 > 1.976 and a significant value of 0.047 < 0 0.05, service quality has a positive and significant effect on purchasing decisions with t count 6.463 > t table 1.976 where sig. 0.000 < 0.05. This is evidenced from the results of the f test where f count > f table with a significance value < 0.05, namely 26.950 > f table 2.665 and sig 0.000 <0.05 which states that promotion and service quality have a positive and significant effect simultaneously on purchasing decisions at PT Tasindo Total Inproducts Batam.